Predicting Future Health Demands in United Arab Emirates - Al-Utaibi, Ghassan; Albloush, Ahmad; Taha, Sadi; Nassoura, Abdelrahim; Albasheer, Omar; Masoud, Najeb; Awwad Mohamed, Mona (International Journal of Psychosocial Rehabilitation, 2020)
This research suggests an information system for improving the health sector in the United Arab Emirates (UAE). A structure for the information system is proposed using regression analysis. Projections for the year 2028 highlight the need for further improvement of health care services in the UAE. This article highlights aspects aiming to improve health care, and it suggests significant actions that could be implemented in the context of the UAE health sector. This study is valuable because it could inspire researchers, practitioners, and policymakers to expand and initiate innovative interventions in the health sector in the UAE.